1975
DOI: 10.1002/bjs.1800621020
|View full text |Cite
|
Sign up to set email alerts
|

Is a “second look operation” justified in suspected recurrences after abdominal cancer surgery?

Abstract: Seventy-three patients have been submitted to 74 further laparotomies for suspected recurrent malignant abdominal disease over a period of 13 months. The original tumour was situated in the large bowel in 42, oesophagus or stomach in 24, ovary in 3, small intestine in 2 and pancreas and retroperitoneum in 1 instance each. There were 10 examples of benign lesions, 16 of further primary cancer and 24 of resectable local recurrences or metastases. Seventeen patients underwent some palliative procedure, and only 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Which approach was to be preferred remained unknown. At the beginning of the 1970s, encouraging results in terms of overall survival were reported and were attributed to the second-look strategy, although controversial results have subsequently been published without any further findings supporting additional surgery without the evidence of recurrent disease [11][12][13].…”
Section: The History Of Metastasectomy In Crcmentioning
confidence: 99%
“…Which approach was to be preferred remained unknown. At the beginning of the 1970s, encouraging results in terms of overall survival were reported and were attributed to the second-look strategy, although controversial results have subsequently been published without any further findings supporting additional surgery without the evidence of recurrent disease [11][12][13].…”
Section: The History Of Metastasectomy In Crcmentioning
confidence: 99%
“…Resection of recurrent cancer after potentially curative resection of colorectal cancer was believed to sometimes lead to "cure" [23][24][25] 1974-80: CEA was shown to detect asymptomatic recurrence of colorectal cancer 10 Methods of detection, imaging, and surgical resection have changed over the intervening 20 years and those committed to resecting metastases may well regard the results of the restored CEA Second Look trial as irrelevant. We take a different view.…”
Section: -78mentioning
confidence: 99%
“…In 1975, Ellis et al first reported the second-look operation for RePC, a palliative gastrojejunostomy for gastric outlet obstruction but not a curative ReOP. 8 The first retrospective study of curative ReOP was performed by Nakeeb et al in 1995 and included 27 patients who underwent pancreaticoduodenectomy. 9 Since then, studies of ReOP with various designs have been conducted, 10–12 but no randomised controlled trials (RCTs) had been published at the time of our pilot screening.…”
Section: Introductionmentioning
confidence: 99%